2012
DOI: 10.1111/j.1420-9101.2012.02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parental radiation exposure on developmental instability in grasshoppers

Abstract: Mutagenic and epigenetic effects of environmental stressors and their transgenerational consequences are of interest to evolutionary biologists because they can amplify natural genetic variation. We studied the effect of parental exposure to radioactive contamination on offspring development in lesser marsh grasshopper Chorthippus albomarginatus. We used a geometric morphometric approach to measure fluctuating asymmetry (FA), wing shape and wing size. We measured time to sexual maturity to check whether parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 141 publications
(235 reference statements)
1
6
2
Order By: Relevance
“…Fluctuating asymmetry has also been indicated as a general indicator of individual quality (Lajus et al, 2015). However, these results are contrary to recent literature on radiation impacts on fluctuating asymmetry in grasshoppers in areas surrounding Chernobyl (Beasley et al, 2012). Beasley et al (2012) indicated no radiation‐induced differences in levels of fluctuating asymmetry in the Chernobyl grasshoppers exposed to several chronic low doses (0.03–50.06 µSv h −1 ).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Fluctuating asymmetry has also been indicated as a general indicator of individual quality (Lajus et al, 2015). However, these results are contrary to recent literature on radiation impacts on fluctuating asymmetry in grasshoppers in areas surrounding Chernobyl (Beasley et al, 2012). Beasley et al (2012) indicated no radiation‐induced differences in levels of fluctuating asymmetry in the Chernobyl grasshoppers exposed to several chronic low doses (0.03–50.06 µSv h −1 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Critical impacts of radiation include impacts on gonads, heritable mutations, and developmental abnormalities (ICRP, 2008). Mutagenic and epigenetic effects can also have transgenerational consequences, providing a source for heritable phenotypic variation (Beasley et al, 2012). Compared to vertebrates, data on invertebrates have been sparse and poorly characterized, even though invertebrates represent ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptation to radiation stress has been reported in the literature. For example, transgenerational developmental responses to radiation have been documented in grasshoppers in Chernobyl [ 20 ], and possible adaptation to oxidative stress in birds as a consequence of the Chernobyl accident has been reported recently [ 21 ]. In regions with high natural radiation levels, radiation resistance has been observed in Drosophila [ 22 ] and other organisms [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[26,27] 2 | EXPERIMENTAL Mortar for making the concrete specimens was prepared using ordinary Portland cement, river sand, and distilled water at a weight ratio of 1:2.5:0.5. [28,29] The mortar was put into moulds with dimensions 100 mm × 100 mm × 100 mm, and Q235 steel rods, diameter 10 mm, were placed in the centres of the moulds subsequently, and used for electromigration experiments. The concrete specimens were demoulded 24 h later, covered with wet towels for 7 days, and cured at room temperature for 28 days.…”
Section: Many Methods Can Be Used To Research the Migration Behaviourmentioning
confidence: 99%